Media Influence: Cognitive and Psychological Markers (On Chinese Medical and Cosmetic Advertising Texts) - Shmeleva, Olga D. (2020)
The main extralinguistic markers of influence in the Chinese medical and cosmetic advertising media discourse are nonverbal, linguocultural conceptual, cultural and historical, cognitive and psychological markers. The article is devoted to a research of cognitive and psychological markers of influence. In the article the most frequency cognitive and psychological markers of influence in the Chinese medical and cosmetic media advertising become known: the built-in messages (unusual decision, motivation to activity, conversations with others and stories about others). The fact that such markers as metaphorical communication and expansion of mass media images, consciousness fragmentation are more significant for the Chinese linguistic culture is established. The research clearly demonstrates that such markers of influence as choice illusion, destruction of time feeling and activization of submodalities are less common in the Chinese medical and cosmetic media advertising. The article contributes to the development of discursive linguistics, psycholinguistics, sociolinguistics, cultural linguistics, discourse theory and influence theory, media linguistics on the example of advertising media, lexicology and Chinese language stylistics.